2016
DOI: 10.1371/journal.pone.0145127
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Origins of Lung Ageing: Early Life Exposures and Lung Function Decline in Adulthood in Two European Cohorts Aged 28-73 Years

Abstract: ObjectivesEarly life environment is essential for lung growth and maximally attained lung function. Whether early life exposures impact on lung function decline in adulthood, an indicator of lung ageing, has scarcely been studied.MethodsSpirometry data from two time points (follow-up time 9–11 years) and information on early life exposures, health and life-style were available from 12862 persons aged 28–73 years participating in the European population-based cohorts SAPALDIA (n = 5705) and ECRHS (n = 7157). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 49 publications
2
56
1
1
Order By: Relevance
“…Our finding also agrees with those of the two recent European multi-center cohort studies, which showed an association between lung function decline and birth season [9].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding also agrees with those of the two recent European multi-center cohort studies, which showed an association between lung function decline and birth season [9].…”
Section: Discussionsupporting
confidence: 93%
“…However, the potential impact of early life factors on lung function decline has been scarcely studied. Nevertheless, data from two recent European cohort studies (SAPALDIA and ECRHS) showed early life factors could predict lung function decline in old age [9]. Taken together, the data from these studies revealed that the season of birth, higher maternal age at delivery, maternal smoking, and the presence of younger siblings Figure 2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Children growing up in smokers’ households tend to become smokers themselves, which could add to lung function loss initially induced by maternal smoking . Further, maternal smoking appeared to aggravate effects of own smoking .…”
Section: Models Of Active Cigarette Smoking During Pregnancymentioning
confidence: 99%
“…In preschool children, the prevalence of asthma related symptoms, such as wheezing and shortness of breath, is even higher . Results of birth cohort studies of the last decades suggest that part of the origins of childhood asthma occur in early life . Lower lung function or asthma in childhood might predispose to chronic obstructive respiratory diseases, including COPD, in adolescence and adult life .…”
Section: Introductionmentioning
confidence: 99%